Prevalence and Detection of qac Genes from Disinfectant-Resistant Staphylococcus aureus Isolated from Salon Tools in Ishaka Town, Bushenyi District of Uganda - Solange Gahongayire; Adamu Almustapha Aliero; Charles Drago Kato; Alice Namatovu (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bacterial infections are on a rise with causal-resistant strains increasing the economic burden to both patients and healthcare providers. Salons are recently reported as one of the sources for transmission of such resistant bacterial strains. The current study aimed at the identification of the prevalent bacteria and characterization of quaternary ammonium compound (qac) genes from disinfectant-resistant S. aureus isolated from salon tools in Ishaka town, Bushenyi District of Uganda. A total of 125 swabs were collected from different salon tools (combs, brushes, scissors, clippers, and shaving machines), and prevalent bacteria were isolated using standard microbiological methods. Identification of isolated bacteria was done using standard phenotypic methods including analytical profile index (API). Susceptibility patterns of the isolated bacteria to disinfectant were determined using the agar well diffusion method. Quaternary ammonium compound (qac) genes (qacA/B and qacC) associated with disinfectant resistances were detected from disinfectant-resistant S. aureus using multiplex polymerase chain reaction (PCR) and Sanger sequencing methods. Of the 125 swab samples collected from salons, 78 (62.4%) were contaminated with different bacteria species. Among the salon tools, clippers had the highest contamination of 20 (80.0%), while shaving machines had the lowest contamination of 11 (44.0%). The most prevalent bacteria identified were Staphylococcus epidermidis (28.1%) followed by S. aureus (26.5%). Of all the disinfectants tested, the highest resistance was shown with sodium hypochlorite 1%. Out of the eight (8) disinfectant-resistant S. aureus analysed for qac genes, 2 (25%) isolates (STP6 and STP9) were found to be qacA/B positive, while 2 (25%) isolates (STP8 and STP9) were found to be qacC gene positive. This study has shown that bacterial contamination of salon tools is common, coupled with resistance to disinfectants with sodium hypochlorite resistance being more common. Furthermore, observed resistance was attributed to the presence of qac genes among S. aureus isolates. A search for qac genes for disinfectant resistance from other bacteria species is recommended.